PARTISIPASI POLITIK MASYARAKAT ADAT DALAM FORMULASI KEBIJAKAN (Deskripsi tentang Partisipasi Politik Masyarakat Kampung Kuta dalam Formulasi Kebijakan di Desa Karangpaninggal Kecamatan Tambaksari Kabupaten Ciamis) - Akhmad Satori; Taufik Nurohman (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Political participation is the participation of society or certain parties in political activities. And when politics is defined as a policy and when we associate with public participation then we will arrive at how public participation in making a policy. Politics Partisipas actively in policy-making becomes an absolute requirement, since participation would give birth control community over the course of government. This study aimed to describe the political participation of indigenous village of Kuta in public policy formulation in the Village District Karangpaningal Tambaksari Ciamis district. Research method used is descriptive qualitative method. In this study the techniques of data collection was done by in-depth interviews (Indeepth Interview), direct observation and documentation, purposive sampling technique is a technique used for sampling. Data analysis using the method of interactive analysis and validity of data used is the technique of data triangulation. The results of this study show that, this result shows that the growing political participation of indigenous peoples in the village of Kuta in policy formulation can be viewed in two processes. First, political participation in the process of internal policies in indigenous communities, and second, political participation in policy formulation processes at the village level. Political participation in indigenous communities, are more closed to the elitist model, Kuncen was instrumental in setting policy, while in access planning, policy control indigenous communities are not involved at all, it is in because of the strength of tradition Kuncen positioned as the main actor who issued the customary policy . While political participation in policy formulation process stages or levels in the Village Karangpaninggal already running with the following democratic values. This means that in this process of political participation open space area .. However, space for perpartisipasi is not utilized optimally. This is because the human resources and the level of understanding of the political partisitisipasi low.